UNDERSTANDING VIETNAMESE PRESERVICE TEFL TEACHERS’ TPACK DEVELOPMENT WITH DESIGN-BASED LEARNING VIA REFLECTIVE LEARNING - Nguyen Bich Dieu; Lee Kean Wah; Tan Choon Keong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The present study is aimed at understanding pre-service teachers’ Technological Pedagogical and Content Knowledge (TPACK) development with Design-based Learning (DBL) in a blended learning course on Technology enhanced learning. Reflection was employed to probe the preservice teachers’ TPACK development and the complex interrelationship between the seven knowledge components. Through content analysis of the participants’ reflective journals and thematic analysis of their interviews, the findings revealed that there was certainly some evidence of growth in some of their TPACK components although content knowledge, technological content knowledge and pedagogical content knowledge were still limited. Both Design-based Learning environment and the reflective tool have proven to be useful platforms for the preservice teachers to enhance their learning experiences of technology use, and their willingness and confidence to apply what they learned in their future teaching practice.